306 Postoperative Navigated Transcranial Magnetic Stimulation to Predict Motor Recovery After Surgery of Tumors Located in Motor Eloquent Areas. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Seidel, Kathleen; Häni, Levin; Lutz, Katharina; Zbinden, Chantal; Redmann, Annetta; Consuegra, Alberto; Raabe, Andreas; Schucht, Philippe
Abstract: INTRODUCTION: Removing the last part of a tumor near eloquent areas potentially puts neurological functions at risk. Knowing whether postoperative deficits are transient is important not only for the patient but also for the neurosurgeon and oncologist. The objective was to analyze the value of postoperative navigated transcranial magnetic stimulation (nTMS) in predicting recovery of motor function and to correlate it to intraoperative motor evoked potential (MEP) monitoring. METHODS: All patients who underwent postoperative TMS mapping within 14 d after surgery for a supratentorial tumor between September 2014 and Decemeber 2017 were selected for analysis. Patients were included if they had a motor deficit of Medical Research Council Grade (MRCS) 0 to 4, regardless of presurgical motor function. Each paretic limb was evaluated separately. Postoperative nTMS MEPs were compared to intraoperative MEPs. RESULTS: nTMS mapping was performed on average 5.4 d after surgery. A positive MEP by nTMS could be elicited in 11 of 15 paretic limbs. Univariate generalized estimating equation analysis yielded a significant prediction of postoperative recovery by a positive MEP response on nTMS with an odds ratio of 11.7 (95% confidence interval 1.04-132, P  = .046). Therefore, if early postoperative TMS elicited an MEP response, recovery would occur in this extremity within 1 mo to at least MRCS 4. If no MEP response could be elicited with 70 to 100% of maximal TMS machine output, 75% of these extremities did not recover significantly. Intraoperative MEP and early postoperative TMS were equally able to predict the likelihood of long-term motor recovery. However, in cases of intraoperative MEP alteration or signal loss, a positive postoperative TMS response could predict a good motor recovery in 80% of extremities. CONCLUSION: Early postoperative nTMS reliably predicts long-term motor recovery of patients suffering from severe motor deficits directly after resection of tumors located in motor eloquent areas.